The Beautiful, the Cheerful, and the Helpful: The Effects of Service Employee Attributes on Customer Satisfaction. Issue 3 (5th February 2013) - Keh, Hean Tat; Ren, Run; Hill, Sally Rao; Li, Xuan
ABSTRACT In contrast to prior studies examining only piecemeal aspects of employee attributes (i.e., physical attractiveness, displayed emotion, or helpfulness), the present research adopts an encompassing approach and considers these attributes simultaneously. These three attributes were selected as they represent the physical, emotional, and motivational aspects of the employee, respectively. This holistic approach provides an understanding of how these three dimensions of employee attributes exert differential effects and interact with one another on customer satisfaction. In order to validate the proposed framework and hypotheses, the authors conducted an experiment as well as a survey in an actual retail setting. Results show that even though all three employee attributes lead to customer satisfaction, employee helpfulness has the strongest impact. In addition, employees' displayed emotion interacts with their physical attractiveness and helpfulness, respectively, to influence customer satisfaction. These findings not only contribute to the literature, but also have managerial implications for high‐contact services.